STRATEGI PENINGKATAN MUTU PELAYANAN PRODUK TABUNGAN HAJI PADA BANK PANIN DUBAI SYARIAH CABANG PALEMBANG - Muhammad Iqbal (Manajemen Keuangan Syariah, 2022)
This research stems from the problem of human resources related to Hajj savings products at one of the Islamic banks in Indonesia, namely Panin Dubai Syariah Bank with the object of research being carried out at the Palembang Branch Office. The problem formulated in this study is how the strategy of developing human resource performance in improving the quality of services for Hajj Savings Products at Panin Dubai Syariah Bank of Palembang Branch. The methodology used with this type of qualitative research. Data mining was carried out using 2 techniques, namely through interviewing informants and documentation. Research respondents were taken by purposive sampling, namely employees and customers of Panin Dubai Syariah Bank at Palembang Branch. The results of this study conclude that the existing performance development strategy at Paof nin Dubai Syariah Bank Palembang Branch includes internship programs, internal seminars (education), as well as education and training. The strategy for improving the quality of services includes cross selling, up selling, and role play. Meanwhile, the strategy to improve product quality includes a home service strategy and a strategy for assisting prospective pilgrims.